Hypoxic, glycolytic metabolism is a vulnerability of B-acute lymphoblastic leukemia-initiating cells - Morris, Vivian; Wang, Dahai; Li, Zhiheng; Marion, William; Hughes, Travis; Sousa, Patricia; Harada, Taku; Sui, Shannan Ho; Naumenko, Sergey; Kalfon, Jérémie; Sensharma, Prerana; Falchetti, Marcelo; et al. (Cell reports (Cambridge), 2022)
High-risk forms of B-acute lymphoblastic leukemia (B-ALL) remain a therapeutic challenge. Leukemia-initiating cells (LICs) self-renew and spark relapse and therefore have been the subject of intensive investigation; however, the properties of LICs in high-risk B-ALL are not well understood. Here, we use single-cell transcriptomics and quantitative xenotransplantation to understand LICs in MLL-rearranged (MLL-r) B-ALL. Compared with reported LIC frequencies in acute myeloid leukemia (AML), engraftable LICs in MLL-r B-ALL are abundant. Although we find that multipotent, self-renewing LICs are enriched among phenotypically undifferentiated B-ALL cells, LICs with the capacity to replenish the leukemic cellular diversity can emerge from more mature fractions. While inhibiting oxidative phosphorylation blunts blast proliferation, this intervention promotes LIC emergence. Conversely, inhibiting hypoxia and glycolysis impairs MLL-r B-ALL LICs, providing a therapeutic benefit in xenotransplantation systems. These findings provide insight into the aggressive nature of MLL-r B-ALL and provide a rationale for therapeutic targeting of hypoxia and glycolysis. [Display omitted] •MLL-r B-ALL cells are varied, with a defined population enriched in initiating cells•MLL-r B-ALL-initiating cells are plastic, emerging from more differentiated states•MYC-driven metabolic heterogeneity may provide a therapeutic opportunity Morris et al. use single-cell transcriptomics to identify a candidate-initiating cell in B-acute lymphoblastic leukemia (B-ALL) with rearrangement of the KMT2A/MLL1 locus (MLL-r), finding that this population is plastic and exists in a hypoxic state that can be pharmacologically targeted.